Adult Laryngeal Ossified Hemangioma: Difficulties in Differential Diagnosis. Issue 8 (November 2018) - Aluffi Valletti, Paolo; Toso, Andrea; Gorris, Christel; Dell'Era, Valeria; Golinelli, Gloria; Pia, Francesco
Abstract : Abstract: Adult laryngeal hemangiomas are uncommon and often poorly symptomatic. The authors describe a laryngeal hemangioma with acute airway obstruction and radiologic findings suggesting a chondrosarcoma-like neoplasm, while pathologic features were consistent with an ossified hemangioma. The presence of fields of bone metaplasia into a classical cavernous hemangioma is an unusual phenomenon which, to our knowledge, was never previously described in the larynx. Difficulties concerning the differential diagnosis and modality of treatment are also discussed.